Knee osteoarthritis risk is increased 4-6 fold after knee injury – a systematic review and meta-analysis. Issue 23 (9th May 2019) - Poulsen, Erik; Goncalves, Glaucia H; Bricca, Alessio; Roos, Ewa M; Thorlund, Jonas B; Juhl, Carsten B
Abstract : Objective: To estimate knee osteoarthritis (OA) risk following anterior cruciate ligament (ACL), meniscus or combined ACL and meniscus injury. Design: Systematic review and meta-analysis. Data sources: MEDLINE, Embase, SPORTDiscus, CINAHL and Web of Science until November 2018. Eligibility criteria for selecting studies: Prospective or retrospective studies with at least 2-year follow-up including adults with ACL injury, meniscal injury or combined injuries. Knee OA was defined by radiographs or clinical diagnosis and compared with the contralateral knee or non-injured controls. Study appraisal and synthesis: Risk of bias was assessed using the SIGN50 checklist. ORs for developing knee OA were estimated using random effects meta-analysis. Results: 53 studies totalling ∼1 million participants were included: 185 219 participants with ACL injury, mean age 28 years, 35% females, 98% surgically reconstructed; 83 267 participants with meniscal injury, mean age 38 years, 36% females, 22% confirmed meniscectomy and 73% unknown; 725 362 participants with combined injury, mean age 31 years, 26% females, 80% treated surgically. The OR of developing knee OA were 4.2 (95% CI 2.2 to 8.0; I 2 =92%), 6.3 (95% CI 3.8 to 10.5; I 2 =95%) and 6.4 (95% CI 4.9 to 8.3; I 2 =62%) for patients with ACL injury, meniscal injury and combined injuries, respectively. Conclusion: The odds of developing knee OA following ACL injury are approximately four times higher compared with a non-injured knee. A meniscal injury and a combined injury affecting both the ACL and meniscus are associated with six times higher odds compared with a non-injured knee. Large inconsistency (eg, study design, follow-up period and comparator) and few high-quality studies suggest that future studies may change these estimates. Clinical relevance: Patients sustaining a major knee injury have a substantially increased risk of developing knee OA, highlighting the importance of knee injury prevention programmes and secondary prevention strategies to prevent or delay knee OA development. PROSPERO registration number CRD42015016900